PP-016 Validation of a new method of sterility testing for the vitamin and lipid mixtures destined for the neonatalogy department. (24th March 2015) - Thévenet, S; Mourad, M; Bermudez, E; Chanat, C; Malin, L; Alaaouch, I; Casetta, A; Poupet, H; Brunet, M; Chast, F
Abstract : Background: Three vitamin and lipid mixtures are produced by the parenteral nutrition unit. Besides the checks performed on these preparations, a membrane filtration sterility test (STERITEST) is carried out as required by the European Pharmacopoeia (EP). Due to constraints associated with these tests (duration, visual interpretation) alternative methods are available such as those for septicaemia diagnosis: Bact/ALERT 3D. It consists of directly inoculating a culture medium followed by automated microbial detection. This method doesn't meet all the criteria required by the EP, but seems acceptable if validated. Purpose: To compare the two methods and to assess their respective efficiency. Material and methods: Growth promotion tests of aerobic, anaerobic micro-organisms (MO) and fungi were performed with 5 colony-forming units (CFUs) of S. aureus, B. subtilis, C. sporogenes, A. brasiliensis, C. albicans, and P. aeruginosa seeded in two different media. Afterwards the three kinds of mixture were produced in a microbiological safety cabinet. Both methods were tested at the same time on three samples of each MO and mixture (54 pairs of samples). Daily readings and identifications of MO were then performed in collaboration with the bacteriology department. The averages of the growth period of each method were compared using a t-test. Results: 100% of MO seeded on the 54 pairs of Bact/ALERT were detected versus 91% on STERITEST. The t-test showed a significant difference between the two methods: the average growth period with STERITEST (5.8 days) was longer than that with Bact/ALERT (2.5 days) (p = 1.27 E-18). Conclusion: Bact/ALERT is more efficient than STERITEST for the detection of MO: increased sensitivity and reproducibility, faster detection and identification of MO, less bias of reading. All these reasons drove us to choose the new BacT/ALERT sterility test instead of STERITEST. Reference: European Pharmacopoeia 7.7 sterility 2.6.1 No conflict of interest.